The Production of Corn Kernel Miso Based on Rice-koji Fermented by Aspergillus oryzae and Rhizopus oligosporus - Diah Ratnaningrum; Thelma Agustina Budiwati; Tri Darsini; Panji Cahya Mawarda (Universitas Gadjah Mada, 2018)
The suitability of corn kernel as raw material to produce miso fermented by rice-koji containing Aspergillus oryzae and Rhizopus oligosporus has been investigated. The optimization was conducted on two important factors in miso production namely mold composition in rice-koji and salt concentration. The mold composition was prepared by inoculating the spores of 2% A. oryzae, 2% R. oligosporus, and 2% the mixture of both in a ratio of 1:1, 2:1, and 1:2 (v/v) into different rice media. The mold composition was optimized to produce rice-koji with high α-amylase and protease activity. Different NaCl concentrations of 10%, 15%, and 20% were subjected to optimization process and added to each mixture after five days of fermentation. The salt concentration was also optimized to produce corn kernel miso with high glucose and high dissolved protein concentration. The result showed that rice-koji containing A. oryzae and R. oligosporus in the ratio of 1:1 had the highest α-amylase and protease activity of 0.42 U/mL and 0.45 U/mL respectively. In addition, the presence of 10% NaCl in corn kernel miso fermented by A. oryzae and R. oligosporus in the ratio of 1:1 exhibited the highest glucose and dissolved protein concentration of 0.64 mg/mL and 8.80 mg/mL respectively. The optimized corn kernel miso by A. oryzae and R. oligosporus in the ratio of 1:1 with 10% NaCl was subjected to nutrient content analysis and compared to the result before the corn kernel was fermented. The nutrient content analysis showed nutrient enhancement after corn kernel was fermented and transformed into a miso. Glucose, dissolved protein, and fat content increased 6.74, 1.34, 7.63 times respectively. This study concludes corn kernel could be utilized to produce a novel corn kernel miso for dietary diversification and for improving nutritional and health status.